CONDITIONS OF FORMATION OF INTEREST IN EDUCATIONAL EXPERIMENTAL WORK IN GRADUATES PEDAGOGICAL GYMNASIUMS (Pedagogy of Higher and Secondary Education, 2000)
The formation of the research interest may by effective enough if the close connection of the educational-cognitive and educational-research activities of pupils. Depending on the profound, process and reasons side of educational-research work didactic conditions must by organized by considerations of opportunities, abilities, and experience of pupils educational-cognitive activities,